Research progress on treatment of extramedullary multiple myeloma. Issue 1 (1st January 2021) - Chen, Yue; Tao, Shandong; Zheng, Xinqi; Shi, Yuye; Zhang, Lijuan; Chen, Kankan; He, Zhengmei; Wang, Chunling; Yu, Liang
ABSTRACT : Objectives: Extramedullary multiple myeloma (EMM) is a relatively less frequent subentity of multiple myeloma (MM) and is generally considered to be a poor prognostic factor. Novel agents and hematopoietic stem cell transplantation (HSCT) have led to a significant improvement in the progression-free survival and overall survival of patients with MM, but outcomes of EMM remain dismal. Little is known regarding the role of novel therapies in this setting. This review summarizes the current available data regarding the roles of proteasome inhibitors, immunomodulators, monoclonal antibodies, chimeric antigen receptor (CAR)-T cell therapy and HSCT in EMM. Methods: A systematic literature review through PubMed was conducted to summarize the published evidence on the therapeutic developments of novel agents and HSCT in EMM. Literature sources published in English were searched, using the terms multiple myeloma, extramedullary and treatment. Results: Long-term outcomes of EMM patients remain dismal despite the utilization of novel agents and HSCT. The standard therapy of EMM has not been established. EMM should be managed as high-risk disease and treated accordingly. Discussion and conclusion: This review will provide an insight on the current and emerging treatment strategies as well as their efficacy in EMM. Further subgroup analyses in large prospective trials focusing on EMM is needed to help optimize the therapy.